Temperature dependence of analogue/RF performance, linearity and harmonic distortion for dual‐material gate‐oxide‐stack double‐gate TFET. Issue 6 (12th March 2021) - Kumar, Satyendra
Abstract: This article presents an investigation report of the effects of temperature variation in the range of 300 to 480 K on electrical performance parameters of conventional dual‐material double‐gate tunnel field effect transistor (DMDG‐TFET) and dual‐material gate‐oxide‐stack double‐gate tunnel field effect transistor (DMGOSDG‐TFET). This report shows an analysis and comparison of the impacts of operating temperature variation on both the devices in terms of DC, analogue/RF, linearity and harmonic distortion parameters with the help of simulation results obtained using a numerical device simulator. It could be stated that DMGOSDG‐TFET is more insensitive with respect to temperature variation in terms of DC, analogue/RF and linearity performances as compared to conventional DMDG‐TFET. Moreover, in terms of harmonic distortion characteristics DMGOSDG‐TFET is found to be more stable with temperature variation as compared to DMDG‐TFET.